Kepulangan, Penerimaan Diri, Dan Aktualisasi: Analisis Teori Humanistik Pada Film Pendek Kai “Pulang” - Ramadani, Wulan; Yunitasari, Andi Putri; Qudratullah, Qudratullah (Journal of Innovative and Creativity, 2026)
The short film "PULANG" produced by PT Kereta Api Indonesia KAI depicts the inner journey of a 65-year-old former convict who faces past trauma and social stigma and struggles to achieve self-actualization with the support of his family and the surrounding community. Analysis using the humanistic theories of Abraham Maslow and Carl Rogers shows how the main character struggles to fulfill basic psychological needs such as security, unconditional acceptance, and self-esteem to achieve recovery and reconciliation. This film functions as a medium for social da'wah that elevates the values ​​of humanity, empathy, and respect for human dignity regardless of the past, and invites the audience to understand the importance of inclusivity and social empowerment. This qualitative study confirms that the film "PULANG" is effective as an educational tool and social reflection, connecting universal values ​​with the local cultural context of the Eid homecoming tradition in Indonesi